Thickness and scratch resistance of adsorbed film formed by triblock symmetrical copolymer solutions. (1st February 2016) - Kosasih, B.; Novareza, O.; Zhu, H.; Taheri, R.; Lin, B.; Tieu, A. K.
Abstract: The thickness and scratch resistance of adsorbed films formed on mild steel samples (MS1020), which have been immersed in water copolymer solutions, are reported. The effects of bulk temperature and the copolymer structures, normal, poly(ethylene oxide) m ‐poly(propylene oxide) n ‐poly(ethylene oxide) m, and reverse, poly(propylene oxide) n ‐poly(ethylene oxide) m ‐poly(propylene oxide) n, are elucidated. The films' thicknesses are independent of structure but not of temperature. The adsorbed films of above cloud point solutions are thicker than below cloud point. However, nanoscratch experiments carried out to measure the scratch resistance of the films reveal that despite of thicker film formed by above cloud point solutions, it is relatively more prone to being detached than the thinner films of below cloud point solutions. The effect of extreme pressure additive, alkyl phosphate ester (APE), is also investigated suggesting the normal copolymer has comparable scratch resistance with APE when used at below the cloud point. Copyright © 2016 John Wiley & Sons, Ltd.